The Potential Therapeutic Properties of Prunetin against Human Health Complications: A Review of Medicinal Importance and Pharmacological Activities - Patel, Kanika; Patel, Dinesh K. (Drug Metabolism and Bioanalysis Letters, 2022)
Background: Flavonoids are polyphenolic compounds found to be present in nature and abundant in flowers and fruits. Flavonoidal class phytochemicals have gained interest in the scientific field because of their important pharmacological activities. Several scientific studies have revealed anti-bacterial, anti-oxidant, anti-fungal, analgesic, anti-viral, anti-inflammatory, anti-tumor, anti-parasitic and anti-allergic activities of flavonoidal class phytochemicals. Prunetin is an O-methylated isoflavone that belongs to the phytochemical phytoestrogen class, found to be present in licorice, red cherry, soybean and legumes. Methods: Biological potential and pharmacological activities of prunetin have been investigated in the present work through scientific data analysis of numerous scientific research works. Numerous literature databases have been searched in order to collect the scientific information on prunetin in the present work. Pharmacological activities of prunetin have been investigated in the present work through literature data analysis of different scientific research works. Scientific data have been collected from Google Scholar, Google, PubMed, Science Direct and Scopus. Analytical data on prunetin has been collected from literature sources and analyzed in the present work. Results: Scientific data analysis revealed the biological importance of prunetin in medicine. Prunetin was found to be present in the pea, peach, Oregon cherry, skimmed cheese, cheese, cow kefir and goat kefir. Prunetin is also present in the Prunus avium, Andira surinamensis, Butea superba, Dalbergia sympathetica, Ficus nervosa, Pterospartum tridentatum and Pycnanthus angolensis. Pharmacological data analysis revealed the biological importance of prunetin on bone disorders, cancers, especially hepatocellular carcinoma, urinary bladder cancer, gastric cancer, ovarian cancer, human airway, gut health and enzymes. Scientific data analysis revealed biological effectiveness of prunetin for their angiogenic effects, anti-inflammatory, anti-oxidant, antimicrobial, estrogenic and vasorelaxant potential. Analytical data revealed the importance of modern analytical techniques for qualitative and quantitative analysis of prunetin in the scientific fields. Conclusion: Scientific data analysis in the present investigation revealed the biological importance and pharmacological activities of prunetin in medicine.
Keywords: urinary bladder cancer